PHOTOVOLTAIC CHARGING CONTROLLERUSING MAXIMUM POWER POINT TRACKING WITH INCREMENTAL CONDUCTANCE METHOD - Asran, Asran; Kartika, Kartika; Jannah, Misbahul; Anni Ritonga, Raisah; Dani, Firwan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Photovoltaic functions to convert solar energy into electrical energy. The use of photovoltaic requires a charging controller to improve the performance of PV to be more optimal. The parts of the charging controller consist of a DC-DC converter and maximum power point tracking (MPPT). DC DC converter is used to change the value of the output voltage of the photovoltaic to reach the peak power of the photovoltaic. To determine the peak power value of photovoltaic, MPPT is needed with incremental conductance algorithm. The DC-DC converter uses a buck converter type with a switching frequency of 150kHz and an inductor of 35µH. The incremental conductance algorithm embedded in the microcontroller works by comparing changes in current and voltage to get the peak power value. The result of this microcontroller is a pulse wave whose duty cycle varies based on the results of the algorithm. This pulse wave will control the buck converter. From the results of this study the charging controller is able to work by changing the value of the duty cycle according to the PV conditions when absorbing power.